Analysis of logging area for agricultural purposes in Gua Musang and Lojing district, Kelantan year 2004 and 2014 using spot 6 images - Ahmad Rafik, Mohd Dzahari (2016)
In efforts to improve the agricultural sector, the opening of new areas through logging activities within a country is inevitable. Among the areas that turned into logging areas for agricultural purposes is Gua Musang and Lojing district in Kelantan. Uncontrolled opening of new area has resulted in environmental problems such as extinction of flora and fauna (destruction biodiversity), land degradation, floods, air pollution and temperature increase. The study was conducted to classify agriculture crops cultivated in Gua Musang and Lojing district and to investigate logging rates for agricultural purposes form year 2004 to 2014 using SPOT-6 satellite image. The result showed that there were changes in forested areas that was converted for agriculture in Gua Musang and Lojing district after 10 years. Maximum Likelihood classifier was used in order to classify land use classes prior to changes detection of conversion from forest to agricultural areas. Classification results showed that in 2004, the total area of primary forest and secondary forest area was 640,882.65 ha. Oil palm was the highest agricultural crops converted from forest (88%), followed by rubber (1%), horticulture (0.44%), mixed horticulture (0.03%) and herbs (0.02%). In conclusion, SPOT 6 images can be used to quantify and analyze logging rates for agricultural purpose to an acceptable accuracy.